Anomaly Detection in VPN (Virtual Private Network) Access Using Machine Learning Algorithms - Ari Budi Prasetiyo; Hari Soetanto; Danang Harito Wibowo (CV. Syntax Corporation Indonesia, 2025)
This research discusses the physical and spatial characteristics of the Ahmad Djuhara Creative Space which is located in the Cirebon City State Building, West Java. In this research, the author uses a qualitative-descriptive research method by studying building characteristics with the architectural characteristics theory by N. John Habraken academically. The Ahmad Djuhara Creative Space building functions as a typical arts and culture workshop from Cirebon. From the study that has been carried out, it is concluded that what forms the physical and spatial character of the Ahmad Djuhara Creative Space building is the roof which has a repeating triangular shape, where the shape of the roof looks different from similar buildings.